PELATIHAN PEMBUATAN BUSSINESS MODEL CANVAS GUNA PENINGKATAN SKILL ENTERPRENEUR DI SMK - Sunarmintyas, Lies; Vernia, Dellia Mila; Alifah, Siti (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
In this globalization era, the mindset of many people has changed, which originally competed to become employees, now many aspire to become entrepreneurs (entrepreneurs). But after they jumped in and tried it, there were many obstacles / obstacles that they experienced as entrepreneurs. As an example of difficulties in the field of consumer segmentation, availability of raw materials, capital and other problems. Therefore, in dealing with these problems training is needed in making proposals with the Business Model Canvas (BMC). The purpose of making the model is to anticipate if it finds difficulties in the business so that it can be overcome immediately. The BMC describes what businesses are being built / carried out thoroughly from various aspects. As a next step, many things that start-up entrepreneurs have never thought of will be summarized in the complete business model. The problems faced by vocational students include knowledge and counseling about entrepreneurship and interest in becoming entrepreneurs. The method used in the implementation of activities is observation, direct interviews, counseling and carrying out demonstrations in front of students. The purpose of community service activities is to provide benefits for Siswak SMK on entrepreneurship and provide understanding and training for vocational students about Business. Model Canvas (BMC). The results achieved are students get knowledge about BMC and are able to plan business with BMC models.